STUDI FENOMENOLOGI TENTANG PENGALAMAN KOMUNIKASI ANAK PELAKU KLITIH - Mahendra, Yushak; Riyanto, Buddy; Herawati, Dewi Maria (Solidaritas, 2025)
The klitih phenomenon is an act of violence or criminality committed by children or adolescents, which has become a social problem that disturbs the local community. One of the klitih phenomena occurs in Pokak Village, Ceper District, Klaten Regency. Where the city of Klaten is one of the cities that has high crime in Central Java, and the majority of the perpetrators of criminal acts are teenagers who are still in school education. Researchers are interested in examining the communication experience of children who commit klitih. This study aims to describe social communication in the Communication Experience of Klitih's Child Perpetrators. The method used in this research is a qualitative research method with a phenomenological approach that aims to explore phenomena related to the communication experience of children who commit klitih. Data collection in this study was carried out through interviews with klitih perpetrators, parents, and siblings as well as observation and documentation to support the interview results. The results of this study found that children who commit klitih tend to have communication experiences that are influenced by negative factors from their social environment, such as peer group pressure, lack of emotional support from family, and lack of positive interaction in the community. Keywords: Communication Experience, Family, Klitih Children